Paclobutrazol induces tolerance in tomato to deficit irrigation through diversified effects on plant morphology, physiology and metabolism - Pal, Sikander; Zhao, Jiangsan; Khan, Asif; Yadav, Narendra Singh; Batushansky, Albert; Barak, Simon; Rewald, Boris; Fait, Aaron; Lazarovitch, Naftali; Rachmilevitch, Shimon (Scientific reports, 2016)
Dwindling water resources combined with meeting the demands for food security require maximizing water use efficiency (WUE) both in rainfed and irrigated agriculture. In this regard, deficit irrigation (DI), defined as the administration of water below full crop-water requirements (evapotranspiration), is a valuable practice to contain irrigation water use. In this study, the mechanism of paclobutrazol (Pbz)-mediated improvement in tolerance to water deficit in tomato was thoroughly investigated. Tomato plants were subjected to normal irrigated and deficit irrigated conditions plus Pbz application (0.8 and 1.6 ppm). A comprehensive morpho-physiological, metabolomics and molecular analysis was undertaken. Findings revealed that Pbz application reduced plant height, improved stem diameter and leaf number, altered root architecture, enhanced photosynthetic rates and WUE of tomato plants under deficit irrigation. Pbz differentially induced expression of genes and accumulation of metabolites of the tricarboxylic acid (TCA) cycle, γ-aminobutyric acid (GABA-shunt pathway), glutathione ascorbate (GSH-ASC)-cycle, cell wall and sugar metabolism, abscisic acid (ABA), spermidine (Spd) content and expression of an aquaporin (AP) protein under deficit irrigation. Our results suggest that Pbz application could significantly improve tolerance in tomato plants under limited water availability through selective changes in morpho-physiology and induction of stress-related molecular processes.
Gesehen am 23.10.2020